The impact of Corporate Social Responsibility toward Brand Loyalty: Direct or Indirect? - Banuara, Sutan (International Journal of Social and Management Studies, 2021)
The purpose of this study is to explain the effect of brand experience, brand satisfaction, brand trust, and brand loyalty in the relationship between corporate social responsibility and brand loyalty to society and the environment. This research will be useful in providing important information for marketers to the extent that non-marketing activities have an impact on product brands which in turn will increase the company’s revenue performance. This study uses a quantitative approach with data methods using Google Forms electronic questionnaires which are distributed through social media owned by researchers. In this study, the total data collected by 240 respondents were analyzed using SmartPLS 3.2.9. The results showed that not all variables had a significant effect. This study explains the indirect effect of corporate social responsibility on brand loyalty through the mediation of brand trust. However, this study also found that the mediating role of the two mediators is not significant (brand experience and brand satisfaction) in the proposed relationship.